Persepsi Mahasiswa terhadap Brand Image Universitas Muhammadiyah Sidoarjo melalui Instagram @umsida1912 - Oktavia Kusuma Wardani; Ainur Rochmaniah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The development of information technology has changed the way we communicate, including in higher education. This study aims to examine students' perceptions of the brand image of Muhammadiyah University of Sidoarjo (UMSIDA) through Instagram @umsida1912. This study employs a descriptive qualitative method with an observational approach and semi-structured interviews with seven UMSIDA students. The participants were selected based on their active use of Instagram and their following of the @umsida1912 account. The findings reveal that students view the Instagram account @umsida1912 as a reflection of an institution that cares and is committed to the academic and social development of its students. They assessed the content presented as having professional visual quality, consistency in content creation, and the values of Muhammadiyah, which are characteristic of the university, reflected in various posts. However, there was criticism regarding the lack of content variety that reflects the diversity of student activities and campus life as a whole. This study provides important insights for higher education institutions in designing more effective communication and branding strategies through social media. By understanding students' expectations and needs, UMSIDA can optimize the use of Instagram as a tool to strengthen a positive and relevant brand image.